Harmoni Tradisi Dan Syariat: Telaah Bapingit Dalam Pernikahan Adat Banjar Perspektif Maqasid Syariah Al-Syathibi - Muhammad Hafiz Fadhilah (Sharia Journal and Education Center Publishing, 2024)
The bapingit tradition is an integral part of the Banjarnese wedding customs in South Kalimantan, carrying profound meaning. This study aims to contribute to a deeper understanding of the bapingit tradition in the context of Banjarnese weddings by applying the Maqasid al-Shari'ah perspective, as proposed by Al-Shatibi. Al-Shatibi emphasized five objectives of Islamic law: preserving religion, life, intellect, lineage, and property. Through an analysis of various literary sources and empirical data, this study reveals that the bapingit tradition embodies positive values that align with the objectives of Islamic law, such as safeguarding one's honor, strengthening social bonds, and fostering harmonious families. The findings of this research affirm that the bapingit tradition is not merely a local custom but a practice rooted in Maqasid al-Shari'ah principles, making it relevant to be preserved as a cultural heritage that offers holistic benefits to society.